Anti-ulcerogenic activity of dentatin from clausena excavata Burm.f. against ethanol-induced gastric ulcer in rats: Possible role of mucus and anti-oxidant effect - Sidahmed, Heyam Mohamed Ali; Vadivelu, Jamuna; Loke, Mun Fai; Arbab, Ismail Adam; Abdul, Bustamam; Sukari, Mohd Aspollah; Abdelwahab, Siddig Ibrahim (Elsevier, 2019)
Background: Clausena excavata Burm.f. (Rutaceae) has been used for the treatment of stomach disorders including peptic ulcer. Purpose: In this study, we aimed to investigate dentatin isolated from C. excavata Burm.f., for anti-ulcer activity against ethanol ulcer model in rats. Methods: Gastric acid output, ulcer index, serum profile, histological evaluation using Hematoxylin and eosin (HE), periodic acid Schiff base stainings and immunohistochemical localization for heat shock proteins 70 (HSP70) were all investigated. Possible involvement of reduced glutathione (GSH), lipid peroxidation, prostaglandin E2 (PGE2), superoxide dismutase (SOD) enzymes, radical scavenging, and anti-Helicobacter pylori activity were investigated. Results: Dentatin showed anti-secretory activity against the pylorus ligature model and protected the gastric mucosa from ethanol ulceration, as revealed by the improved macroscopic and histological appearance. Dentatin significantly increased the gastric homogenate content of PGE2 GSH and SOD. Dentatin inhibited the lipid peroxidation as revealed by the reduced gastric content of malondialdehyde (MDA). Moreover, dentatin up-regulated HSP70 expression. However, dentatin showed insignificant anti-H. pylori activity. Conclusion: Dentatin possesses gastro-protective activity, which could be attributed to the anti-secretory, mucus production, anti-oxidant, and HSP70 activities.